Leishmania infection in bats from a non-endemic region of Leishmaniasis in Brazil (2017)
Leishmaniasis is a complex of zoonotic diseases caused by parasites of the genus Leishmania, which can develop in domestic as well as wild animals and humans throughout the world. Currently, this disease is spreading in rural and urban areas of non-endemic regions in Brazil. Recently, bats have gained epidemiological significance in leishmaniasis due to its close relationship with human settlements. In this study, we investigated the presence of Leishmania spp. DNA in blood samples from 448 bats belonging to four families representing 20 species that were captured in the Triangulo Mineiro and Alto Paranaiba areas of Minas Gerais State (non-endemic areas for leishmaniasis), Brazil. Leishmania spp. DNA was detected in 8.0% of the blood samples, 41.6% of which were Leishmania infantum, 38.9% Leishmania amazonensis and 19.4% Leishmania braziliensis. No positive correlation was found between Leishmania spp. and bat food source. The species with more infection rates were the insectivorous bats Eumops perotis; 22.2% (4/18) of which tested positive for Leishmania DNA. The presence of Leishmania in the bat blood samples, as observed in this study, represents epidemiological importance due to the absence of Leishmaniasis cases in the region. © Cambridge University Press 2017.